2014
DOI: 10.11648/j.ijefm.20140204.13
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Direct Investment and SME Growth: Highlighting the Need for Absorptive Capacity to Support Linkages between Transnational Corporations and SMEs in Developing Countries

Abstract: FDI has always been thought to affect the growth of local firms through technological spillovers and as such many developing countries have invested a lot to attract FDI. These spillovers can happen through FDI having backward, forward and horizontal linkages with local firms. Though in many countries FDI has contributed to the development of local firms, there is evidence to suggest that this is not always the case. There are instances where FDI has instead driven local firms out of business. The ability of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
1
4
0
3
Order By: Relevance
“…The current findings also agree with Wang, Deng, Kafouros, and Chen (2012) study, which found that different foreign entry modes had a considerable impact on the scope of foreign presence and the productivity outputs of companies in the host country. Additionally, the findings are also in agreement with Lugemwa (2014) who recognized FDI as a critical aspect when it comes to driving growth of the manufacturing sector. The study further supports IMF (2018) observation that foreign direct investment benefits does not appear as expanded resources that can be invested, but it also appears in sharing of knowledge and technology.…”
Section: Discussion Of Results Foreign Direct Investent and Performance Of Manufacturing Firmssupporting
confidence: 89%
See 1 more Smart Citation
“…The current findings also agree with Wang, Deng, Kafouros, and Chen (2012) study, which found that different foreign entry modes had a considerable impact on the scope of foreign presence and the productivity outputs of companies in the host country. Additionally, the findings are also in agreement with Lugemwa (2014) who recognized FDI as a critical aspect when it comes to driving growth of the manufacturing sector. The study further supports IMF (2018) observation that foreign direct investment benefits does not appear as expanded resources that can be invested, but it also appears in sharing of knowledge and technology.…”
Section: Discussion Of Results Foreign Direct Investent and Performance Of Manufacturing Firmssupporting
confidence: 89%
“…Newman, Rand, Talbot & Tarp (2015) evaluated the relationship between technology transfer, foreign investment and productivity spillover and empirically established that certain gains in productivity were linked to direct connection between domestic and foreign owned companies along supply chain. Lugemwa (2014) finds that FDI plays an important role in fostering growth of local manufacturing firms. Leman and Ismet, (2015) noted that FDI inflows has been the main source of economic growth among developing countries.…”
Section: Theoretical and Empirical Literaturementioning
confidence: 99%
“…The transfer of knowledge and technology from multinational enterprises depends on the absorptive capacity of Africa's small and medium-sized enterprises, which often suffer from a high level of informality and information asymmetries. Absorptive capacity -defined as the production and technology gap between domestic and foreign firmsshapes the ability of local firms and small and medium-sized enterprises to benefit from technological spillovers from multinational enterprises (Lugemwa, 2014;Vu, 2018). A recent study on 100 manufacturing firms in Kenya shows that absorptive capacity plays a statistically significant role in FDI's boosting firm performance, implying that firms need some level of knowledge and technology capacity to fully tap the benefits of FDI (Wanjere et al, 2021).…”
Section: Knowledge and Technology Transfermentioning
confidence: 99%
“…Newman, Rand, Talbot & Tarp (2015) evaluated the relationship between technology transfer, foreign investment and productivity spillover and empirically established that certain gains in productivity were linked to direct connection between domestic and foreign owned companies along supply chain. Lugemwa (2014) finds that FDI plays an important role in fostering growth of local manufacturing firms. Leman and Ismet, (2015) noted that FDI inflows has been the main source of economic growth among developing countries.…”
Section: Related Literaturementioning
confidence: 99%